Ratio of X And Y Spermatozoa in Ettawa Crossbred Goats Separated Using The Egg White Albumin Column Sedimentation Method - Kurniawati, Aita; Sumadiasa, I Wayan Lanus; Yuliani, Enny (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Reproduction is one of the important factors in efforts to increase livestock productivity, especially in breeding and genetic improvement programs. This sperm separation technique can be perforsmed using various methods, one of which is using an egg white albumin gradient medium that functions to separate spermatozoa based on differences in weight and speed of movement. This study aimed to determine the ratio of X and Y spermatozoa in Ettawa crossbred goats separated using the egg white albumen method. The material used in this study was fresh semen from PE goats. This study used a completely randomized design (CRD) with three egg white content treatments: (P1): 5% and 25%, (P2): 10% and 30%, and (P3): 15% and 35%. The parameters observed were the X and Y spermatozoa ratio, motility, and viability. Post-separation, in data analysis, the highest proportion of X and Y spermatozoa was found in treatment P2, namely 59.70±5.55% (X) and 40.30±5.55% (Y) in the upper layer and 40.40±6.89% (X) and 59.60±6.89% (Y) in the lower layer. The analysis results showed that the highest average percentage of PE goat spermatozoa motility was found in the top and bottom layers in the P2 treatment, namely (81.10 ± 1.37% and 80.50 ± 1.50%), and the lowest motility was found in the P3 treatment, namely (80.50 ± 1.50% and 79.90 ± 1.66%). In addition, the highest percentage of viability was found in the top and bottom layers in the P2 treatment, namely (82.40 ± 1.83% and 83.10 ± 1.66%). From the results of the study, it can be concluded that there is a significant difference in the ratio of X and Y spermatozoa in Ettawa crossbred goats with three treatments. P2 concentrations of 10% and 30% were proven effective for separating X and Y spermatozoa.